Financial Report Recording System At PT Asuransi Eka Lloyd Jaya - Tutut Alamin; Didik Sofian Haryadi; Titi Christiana (Journal of Engineering, Electrical and Informatics, 2024)
This research aims to design a financial report recording system at PT Asuransi Eka Lloyd Jaya. By creating a financial reporting system, it is hoped that it will make it easier for the bookkeeping department to record financial data, as well as to make reports more quickly, which are used by the insurance company as a management tool for financial activities at PT Asuransi Eka Lloyd Jaya. Likewise, the aim of the research entitled "Financial Report Recording System at PT Asuransi Eka Lloyd Jaya" is to prepare reports that are equipped with data security, namely passwords. The research results of the financial report recording system at PT Asuransi Eka Lloyd Jaya are to make it easier to record cash flows, as well as to make financial reports more quickly and efficiently. The conclusion from the results of this research is that this system can facilitate the activity of recording financial report transactions so that errors do not occur in recording, users can easily present financial reports more quickly so as to minimize recording time and recording errors, and make it easier for users to print payment reports easily. affective and efficient results so that they can support and speed up decision making.